2000
DOI: 10.1210/jc.85.5.2057
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Acts as a Germ Cell Survival Factor in the Human Testis in Vitro

Abstract: The necessity of estrogens for male fertility was recently discovered in studies on both estrogen receptor alpha knockout and aromatase (cyp 19 gene) knockout mice. However, direct testicular effects of estrogens in male reproduction have remained unclear. Here we studied the protein expression of ERalpha and the recently described estrogen receptor beta in the human seminiferous epithelium and evaluated the role of 17beta-estradiol, the main physiological estrogen, in male germ cell survival. Interestingly, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
1
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(179 citation statements)
references
References 0 publications
9
162
1
7
Order By: Relevance
“…There is large augmentation of endogenous estradiol levels; consequently, estradiol/testosterone ratio was higher and may account for the deleterious effect of estradiol on the late steps of spermatogenesis, which do require testosterone [32]. If we take into account the testicular localization of the estrogen receptors (alpha and beta) that are present in both somatic cells and germ cells [37], the negative role of estradiol is conceivable. Since the testicular level of testosterone is high, it is postulated that this androgen could be further aromatized not only in Leydig cells [21] but also in Sertoli cells [17] as well as in germ cells, especially in sperm as shown in rodents [14,18,27] and in humans [24].…”
Section: Discussionmentioning
confidence: 99%
“…There is large augmentation of endogenous estradiol levels; consequently, estradiol/testosterone ratio was higher and may account for the deleterious effect of estradiol on the late steps of spermatogenesis, which do require testosterone [32]. If we take into account the testicular localization of the estrogen receptors (alpha and beta) that are present in both somatic cells and germ cells [37], the negative role of estradiol is conceivable. Since the testicular level of testosterone is high, it is postulated that this androgen could be further aromatized not only in Leydig cells [21] but also in Sertoli cells [17] as well as in germ cells, especially in sperm as shown in rodents [14,18,27] and in humans [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although estradiol is regarded as a female steroid hormone, it circulates in low but measurable levels in human males (1,2). Estradiol has recently been reported to play an important role in male reproductive health.…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol is produced in the testes from aromatized testosterone, and progressive disruption of spermatogenesis and infertility was also observed among aromatase knockout mice (5). A direct role of estradiol as a germ cell survival factor was then demonstrated in the human testis in vitro, where estradiol was shown to inhibit testicular apoptosis much more effectively than testosterone (2). A potential role of nonpersistent pesticides (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol should be also considered as a ''male hormone'' [3,43] and appears to be a potential germ cell survival factor in primate [2,46,62]. Aquila et al first demonstrated ER-alpha and ER-beta concomitant expression in human ejaculated spermatozoa, and suggested that estrogen may be able to influence both capacitation and acrosome reaction [2].…”
Section: Estrogenmentioning
confidence: 99%
“…Aquila et al first demonstrated ER-alpha and ER-beta concomitant expression in human ejaculated spermatozoa, and suggested that estrogen may be able to influence both capacitation and acrosome reaction [2]. Estrogen receptors for both beta and alpha were present in the early meiotic spermatocytes and elongated spermatids of human testis and found that low dose of 17 beta-estradiol was capable of inhibiting germ cell apoptosis [46]. The localization of estrogen receptor beta and aromatases in pachytene spermatocytes was also demonstrated, indicating a role of estrogen in this step of spermatogenesis.…”
Section: Estrogenmentioning
confidence: 99%